Alfvén Wave Mode Conversion in Neutron Star Magnetospheres: A Semianalytic Approach - Alexander Y. Chen; Yajie Yuan; Dominic Bernardi (The Astrophysical Journal, 2025)
We write down the force-free electrodynamics equations in dipole coordinates and solve for axisymmetric normal modes corresponding to Alfvénic perturbations in the magnetosphere of a neutron star. We show that a single Alfvén wave propagating on dipole field lines spontaneously sources a fast magnetosonic (fms) wave at the next order in the perturbation expansion, without needing three-wave interaction. The frequency of the sourced fms wave is twice the original Alfvén wave frequency, and the wave propagates spherically outward. The properties of the outgoing fms wave can be computed exactly using the usual devices of classical electrodynamics. We extend the calculation to the closed zone of a rotating neutron star magnetosphere, and show that the Alfvén wave also sources a spherical fms wave but at the same frequency as the primary Alfvén wave.